System development of ensuring human resource competitiveness - Пляшко, Ольга Степанівна (Technology audit and production reserves, 2016)
In the article the essence of competitiveness support system are defined and its development experience are generalized. It is established that the system of ensuring human resource competitiveness is a methodology for its achieving. It includes theoretical (methodological) and practical level. It is found that features of human resource competiveness, which significantly affect the structural and functional features of its ensuring, are subject-object interaction and determination factor and part of ensuring competitiveness. Two-level system of ensuring human resource competitiveness is offered. It is based on the human resource activity, appropriate environment creation and incentives. Also it includes regulatory and analytical, organizational and socio-economic methods and efforts aimed at increase of human resource competiveness, state economy and human development.